Coating composition, coating film, laminate and sliding member

By using tetrafluoroethylene/hexafluoropropylene copolymer particles and specific binder resins in the coating composition, the problem of insufficient segregation and sliding properties of the fluororesin in the coating film is solved, and the sliding properties and wear resistance are significantly improved.

CN119907839APending Publication Date: 2025-04-29DAIKIN INDUSTRIES LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380067969.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, it is difficult to form a coating film with excellent sliding properties, especially in the mixing of fluororesin and binder resin, it is difficult to mix uniformly and bias the surface of the coating film, resulting in insufficient sliding properties.

Method used

Using a coating composition containing tetrafluoroethylene/hexafluoropropylene copolymer particles, a specific binder resin and a liquid medium, the melt flow rate, melting point and particle size distribution of the particles are controlled to ensure that the fluororesin particles can be biased on the surface when the coating film is formed and the sliding properties are improved.

Benefits of technology

A coating film with excellent sliding properties is achieved, suitable for applications such as sliding members, and the wear resistance and heat resistance of the coating film have also been significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Provided is a coating composition capable of forming a coating film having excellent sliding properties and wear resistance. A coating composition containing tetrafluoroethylene / hexafluoropropylene copolymer particles, a binder resin, and a liquid medium, the coating composition being characterized in that: the binder resin is at least one type selected from the group consisting of a polyamideimide resin, a polyetherimide resin, a polyimide resin, and a polyaryletherketone resin; the tetrafluoroethylene / hexafluoropropylene copolymer particles have a melt flow rate of 10-25 (g / 10 min), a melting point of 270 DEG C or less, and a median diameter (D50) of 0.1-50 [mu] m, and the mass ratio of the tetrafluoroethylene / hexafluoropropylene copolymer particles to the binder resin is 55 / 45-94 / 6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coating composition, a coating film, a laminate, and a sliding member. Background Art

[0002] Fluororesins have excellent sliding properties and heat resistance, and are used in combination with binder resins such as polyamideimide (PAI) and polyimide (PI) for various applications such as sliding components and other industrial components.

[0003] Patent Document 1 discloses a reed valve for an EGR device having a coating film composed of 65 to 75 parts by mass of a polyamide-imide resin, 10 to 20 parts by mass of a fluororesin powder, and 10 to 30 parts by mass of an inorganic powder.

[0004] Patent Document 2 discloses a non-adhesive composition comprising a liquid medium, a fluorine-containing polymer containing a filler, and a polymer binder, wherein the ratio of the fluorine-containing polymer containing a filler to the binder is preferably 15:85 to 30:70 by weight.

[0005] Patent document 3 discloses a composition for cooking utensils or kitchen supplies, characterized in that it contains a fluororesin, a heat-resistant resin, water and a solvent with a boiling point of 235° C. or above, the fluororesin is a tetrafluoroethylene / hexafluoropropylene copolymer, the heat-resistant resin is at least one selected from the group consisting of polyarylene sulfide, polyethersulfone, polyamideimide, polyimide, polyetherimide, polyetheretherketone and aromatic polyester, and the mass ratio of the fluororesin to the heat-resistant resin is 1 / 99 to 30 / 70.

[0006] Patent document 4 discloses a coating composition comprising a fluororesin (A), a polyetheretherketone resin (B), and a binder resin (C) having an amide group and / or an imide group, characterized in that the mass ratio of the fluororesin (A) to the binder resin (C) is (A) / (C)=70 / 30 to 5 / 95, and the polyetheretherketone resin (B) is 3 to 50 parts by mass per 100 parts by mass of the total of the fluororesin (A) and the binder resin (C).

[0007] Patent Document 5 discloses a fluororesin film having a melting point of 200° C. or higher and a melt viscosity of 1×10 10 A fluororesin film of a cured product of a thermosetting polymer containing no fluorine atoms and particles of a tetrafluoroethylene-based polymer having a molecular weight of less than Pa·s, wherein, when the amount of fluorine atoms present on one surface of the fluororesin film as determined quantitatively by energy dispersive X-ray analysis is represented by A and the amount of fluorine atoms present on the other surface is represented by B, B / A is in the range of 0.6 to 1.7.

[0008] Patent Document 6 discloses a fluororesin film comprising: a fluororesin film having a melting point of 200° C. or higher and a melt viscosity of 1×10 10 A tetrafluoroethylene polymer having a molecular weight of less than Pa·s; and particles of a functional compound for adjusting the properties of the tetrafluoroethylene polymer containing at least one specific atom selected from the group consisting of titanium, silicon, magnesium, aluminum, cerium and nitrogen, wherein when the amount of the specific atoms present on one surface of the fluororesin film quantified by energy dispersive X-ray analysis is set to A and the amount of the specific atoms present on the other surface is set to B, B / A is 0.6 to 1.7.

[0009] Patent document 7 discloses a coating composition comprising a heat-resistant binder resin, a hot-melt fluororesin and an organic solvent, wherein the hot-melt fluororesin is a powder having an average particle size of less than 1.0 μm, a melting point of more than 270° C., and a melt flow rate of 15 to 45 g / 10 minutes, and the hot-melt fluororesin is 10 to 200 parts by mass relative to 100 parts by mass of the heat-resistant binder resin.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2012-149610

[0013] Patent Document 2: Japanese Patent Application No. 2002-516618

[0014] Patent Document 3: Japanese Patent Application Publication No. 2020-50878

[0015] Patent Document 4: Japanese Patent Application Publication No. 2007-238686

[0016] Patent Document 5: Japanese Patent Application Publication No. 2020-37661

[0017] Patent Document 6: Japanese Patent Application Publication No. 2020-37662

[0018] Patent Document 7: International Publication No. 2022 / 054916 Summary of the invention

[0019] Problems to be solved by the invention

[0020] An object of the present disclosure is to provide a coating composition capable of forming a coating film having excellent sliding properties.

[0021] Means for solving problems

[0022] The present disclosure relates to a coating composition, which is a coating composition comprising tetrafluoroethylene / hexafluoropropylene copolymer particles, a binder resin and a liquid medium, characterized in that:

[0023] The binder resin is at least one selected from the group consisting of polyamide-imide resin, polyether-imide resin, polyimide resin and polyaryletherketone resin.

[0024] The tetrafluoroethylene / hexafluoropropylene copolymer particles have a melt flow rate of 10 to 25 (g / 10 minutes), a melting point of 270° C. or less, and a median particle size (D50) of 0.1 μm to 50 μm.

[0025] The mass ratio of the tetrafluoroethylene / hexafluoropropylene copolymer particles to the binder resin is 55 / 45 to 94 / 6.

[0026] The liquid medium preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide and N,N-dimethylacetamide.

[0027] The coating composition may further contain a coloring pigment.

[0028] The coating composition may further contain a filler.

[0029] The present disclosure also relates to a coating film, characterized in that it is formed from the above-mentioned coating composition.

[0030] The present disclosure also relates to a laminated body characterized by having a coating film formed from the above-mentioned coating composition on a substrate.

[0031] The above-mentioned substrate is preferably a metal substrate.

[0032] The laminated body may be a sliding member.

[0033] Effects of the Invention

[0034] The coating composition of the present disclosure can provide a coating film having excellent sliding properties, and thus is suitable for use in sliding parts and the like. DETAILED DESCRIPTION

[0035] Hereinafter, the present disclosure will be described.

[0036] Conventionally, coating compositions using fluororesins and binder resins have been used for a wide range of applications. On the other hand, fluororesins are difficult to mix uniformly in a liquid medium, and there is a problem that fluororesins sometimes aggregate and segregate in the resulting coating film. Therefore, it is difficult to highly mix fluororesins, and coating compositions that generally contain a large amount of binder resin are used (e.g., fluorine-containing coating compositions of Patent Documents 1 to 3).

[0037] In such conventional fluorine-containing coating compositions, in many cases, only the binder resin is melted and flowed when forming a coating film, and the fluorine resin particles are maintained dispersed in the binder resin.

[0038] Particularly when fluororesin is PTFE, because viscosity when melting is high, it is difficult to make it melt-flow, and becomes the state dispersed in the matrix resin with the state of particles. If it is such a state, it is difficult to utilize the coating composition mixed with fluororesin in a large amount to form a good coating film.

[0039] On the other hand, in order to obtain the effect of sliding properties, fluororesin is mainly responsible for its performance. Sliding properties are physical properties of the coating surface, so fluororesin can be localized on the coating surface to improve these properties. However, in order to localize the fluororesin on the coating surface, it is necessary to use a fluororesin that is easy to localize.

[0040] In the present disclosure, as the fluororesin, a fluororesin with a relatively low melting point and high fluidity is used, thereby making it possible to mix the fluororesin in a high proportion in the coating composition. Furthermore, since the fluororesin is easy to flow when melted, it is easy for the fluororesin to be localized on the surface of the coating film when the coating film is formed, and high sliding properties that were not available in the conventional fluorine-containing coating composition can be obtained.

[0041] The coating composition disclosed herein is a coating composition comprising tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymer (FEP) particles, a binder resin, and a liquid medium, characterized in that the binder resin is at least one selected from the group consisting of polyamide-imide resins, polyetherimide resins, polyimide resins, and polyaryletherketone resins, the melt flow rate of the FEP particles is 10 to 25 (g / 10 minutes), the melting point is below 270°C, the median particle size (D50) is 0.1 μm to 50 μm, and the mass ratio of the FEP particles to the binder resin is 55 / 45 to 94 / 6.

[0042] In such a coating composition, the FEP resin particles are not dissolved in the solvent in the coating state, and the binder resin is dissolved in the solvent to help form a coating film during coating. In addition, during thermal melting, both the binder resin and the FEP resin melt, thereby forming a coating film. At this time, even in the case of melting, the binder resin and the FEP resin are incompatible, and the FEP resin with lower surface free energy tends to be concentrated on the surface of the coating film. As a result, high sliding properties can be obtained.

[0043] (FEP particles)

[0044] As the above-mentioned FEP, there is no particular limitation, but a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.9 / 1.1 or less. If the TFE unit is too few, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. The above-mentioned FEP is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 mol% to 10 mol%, and the total of TFE units and HFP units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and HFP, perfluoro(alkyl vinyl ether) (PAVE), CF2=CF-OCH2-Rf 2 (Where Rf 2 represents a perfluoroalkyl group having 1 to 5 carbon atoms) and the like.

[0045] Examples of the PAVE include perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE), and perfluoro(propyl vinyl ether) (PPVE).

[0046] The content of each monomer unit in the FEP particles can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.

[0047] Furthermore, the FEP particles used in the present disclosure satisfy the following physical properties. By setting the melt flow rate, melting point and median particle size of the FEP particles to the desired ranges shown below, the FEP particles can be stably mixed into the coating composition at a high level. Furthermore, when the coating film formed by the coating composition is fired, the good dispersibility and fluidity of the FEP particles are maintained, so that the FEP particles are less likely to aggregate and tend to be localized on the surface of the fired coating film, thereby obtaining a coating film with excellent sliding properties.

[0048] The melt flow rate (MFR) of the FEP particles is 10 to 25 (g / 10 minutes), preferably 13 to 23 (g / 10 minutes), and more preferably 15 to 20 (g / 10 minutes). If the MFR is 10 or less, the processability is reduced, and the fluororesin is difficult to be localized on the coating surface, thereby reducing the slip property. If it exceeds 25, the fluidity is high and interlayer delamination may occur.

[0049] In this specification, the MFR is a value obtained as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2 mm and a length of 8 mm per 10 minutes at a measurement temperature (for example, 372° C. in the case of FEP) and a load (for example, 5 kg in the case of FEP) determined according to ASTM D 1238 using a melt indexer (manufactured by Yasuda Seiki Seisakusho, Ltd.).

[0050] The melting point of the FEP particles is lower than 270° C., preferably lower than 265° C., and more preferably lower than 260° C. The lower limit of the melting point is preferably 220° C.

[0051] If the melting point exceeds 270° C., the processing temperature needs to be increased. In this case, the curing of the binder resin tends to proceed, which may hinder the localization of the fluororesin on the coating film surface.

[0052] In this specification, the melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0053] As an indicator of the localization of fluororesin on the coating surface, the surface segregation rate of fluorine atoms on the coating surface can be evaluated by EDX (energy dispersive X-ray analysis). The surface segregation rate of fluorine atoms is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more.

[0054] The friction coefficient of the coating surface can be evaluated by TriboGear (manufactured by Shinto Science Co., Ltd.). The friction coefficient of the coating is preferably less than 0.09, more preferably less than 0.08, and further preferably less than 0.07. In addition, the wear resistance can be evaluated by a reciprocating wear test using Friction Player (manufactured by RHESCA). In accordance with the preferred range of the above-mentioned friction coefficient, the wear resistance at 25°C is preferably more than 1300 seconds, more preferably more than 1400 seconds, and further preferably more than 1500 seconds. Furthermore, the wear resistance at 150°C is preferably more than 600 seconds, more preferably more than 700 seconds, and further preferably more than 800 seconds.

[0055] By having such a friction coefficient and abrasion resistance, a coating film having excellent sliding properties and durability can be obtained, and a coating film suitable for applications requiring sliding properties can be obtained.

[0056] The median particle size (D50) of the FEP particles is 0.1 μm to 50 μm, preferably 0.1 μm to 5 μm, and more preferably 0.1 μm to 1 μm.

[0057] When the median particle size is within the above range, good dispersibility can be exhibited in the obtained coating film, and a film excellent in heat resistance and non-stickiness can be formed on the surface.

[0058] It should be noted that, in this specification, the median particle size refers to the particle size of the particle whose cumulative solid particle amount from the smallest particle reaches 50% of the total solid particle amount (so-called 50% particle size) when the particle size distribution curve of the particle size and the solid particle amount is obtained. The median particle size can be directly measured on the coating composition disclosed in the present invention.

[0059] The thermal decomposition starting temperature of the FEP particles is preferably 360° C. or higher. The thermal decomposition starting temperature is more preferably 380° C. or higher, and even more preferably 390° C. or higher.

[0060] In the coating composition disclosed herein, the mass ratio of the FEP particles to the binder resin is 55 / 45 to 94 / 6. That is, compared with the known fluorine-containing resin coating composition, the FEP particles are highly mixed with the binder resin. If the mass ratio is lower than the lower limit, excellent sliding properties may not be obtained. If the mass ratio exceeds the upper limit, the adhesion of the obtained coating composition to the substrate may become insufficient.

[0061] The mass ratio of the FEP particles to the binder resin is preferably 55 / 45 to 80 / 20, more preferably 60 / 40 to 70 / 30.

[0062] The coating composition of the present disclosure also includes a binder resin.

[0063] The binder resin is preferably a resin having excellent adhesion to the substrate and excellent heat resistance, and specifically, at least one selected from the group consisting of polyamide-imide resins, polyether-imide resins, polyimide resins, and polyaryletherketone resins, and two or more thereof may be used in combination.

[0064] The polyamide-imide resin (PAI) is a resin composed of a polymer having an amide bond and an imide bond in the molecular structure. The PAI is not particularly limited, and examples thereof include: a resin composed of a high molecular weight polymer obtained by the reaction of an aromatic diamine having an amide bond in the molecule with an aromatic tetracarboxylic acid such as pyromellitic acid; a reaction of an aromatic tricarboxylic acid such as trimellitic anhydride with a diamine such as 4,4-diaminophenyl ether or a diisocyanate such as diphenylmethane diisocyanate; a reaction of a dibasic acid having an aromatic imide ring in the molecule with a diamine, etc. As the PAI, it is preferably composed of a polymer having an aromatic ring in the main chain from the aspect of excellent heat resistance.

[0065] The polyetherimide resin (PEI) is a resin composed of a polymer having an ether bond and an imide bond in the molecular structure. As the PEI, there is no particular limitation, and examples thereof include a resin composed of a high molecular weight polymer obtained by reacting 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane with m-phenylenediamine in an organic solvent. As the PEI, from the aspect of excellent heat resistance, it is preferably composed of a polymer having an aromatic ring in the main chain.

[0066] The polyimide resin (PI) is a resin composed of a polymer having an imide bond in the molecular structure. The PI is not particularly limited, and examples thereof include resins composed of high molecular weight polymers obtained by reaction of aromatic tetracarboxylic anhydrides such as pyromellitic anhydride, etc. The PI is preferably composed of a polymer having an aromatic ring in the main chain from the perspective of excellent heat resistance.

[0067] Specific examples of the aromatic polyetherketone resin referred to as the polyaryletherketone resin (PAEK) include polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK), and polyetheretherketoneketone (PEEKK).

[0068] The aromatic polyetherketone resin is not particularly limited as long as it includes a repeating unit composed of an arylene group, an ether group [—O—], and a carbonyl group [—C(═O)—], and for example includes a repeating unit represented by any one of the following formulae (a1) to (a5).

[0069] [-Ar-O-Ar-C(=O)-](a1)

[0070] [-Ar-O-Ar-C(=O)-Ar-C(=O)-](a2)

[0071] [-Ar-O-Ar-O-Ar-C(=O)-](a3)

[0072] [-Ar-O-Ar-C(=O)-Ar-O-Ar-C(=O)-Ar-C(=O)-](a4)

[0073] [-Ar-O-Ar-O-Ar-C(=O)-Ar-C(=O)-](a5)

[0074] (In the formula, Ar represents a divalent aromatic hydrocarbon ring group which may have a substituent.)

[0075] Examples of the divalent aromatic hydrocarbon ring group represented by Ar include phenylene (o-phenylene, m-phenylene, p-phenylene, etc.), arylene groups having 6 to 10 carbon atoms such as naphthylene, biarylene groups (each having 6 to 10 carbon atoms) such as biphenylene (2,2'-biphenylene, 3,3'-biphenylene, 4,4'-biphenylene, etc.), triarylene groups (each having 6 to 10 carbon atoms) such as o-triphenylene, m-triphenylene, p-triphenylene, etc. These aromatic hydrocarbon ring groups may have a substituent, such as a halogen atom, an alkyl group (a linear or branched alkyl group having 1 to 4 carbon atoms such as a methyl group), a haloalkyl group, a hydroxyl group, an alkoxy group (a linear or branched alkoxy group having 1 to 4 carbon atoms such as a methoxy group), a mercapto group, an alkylthio group, a carboxyl group, a sulfo group, an amino group, an N-substituted amino group, a cyano group, etc. In the repeating units (a1) to (a5), the types of Ar may be the same or different from each other. Preferred Ar is phenylene (eg, p-phenylene) or biphenylene (eg, 4,4'-biphenylene).

[0076] As the resin having repeating unit (a1), polyetherketone (for example, "PEEK-HT" manufactured by Victrex) and the like can be exemplified. As the resin having repeating unit (a2), polyetherketoneketone (for example, "PEKK" manufactured by Arkema + Oxford Performance Material) and the like can be exemplified. As the resin having repeating unit (a3), polyetheretherketone (for example, "VICTREX PEEK" manufactured by Victrex, "Vestakeep (registered trademark)" manufactured by Evonik, "Vestakeep-J" manufactured by Daicel Evonik, "KetaSpire (registered trademark)" manufactured by Solvay Speciality Polymers) and polydiphenylether-phenylether-phenylketone (for example, "Kadel (registered trademark)" manufactured by Solvay Speciality Polymers) and the like can be exemplified. As the resin having repeating unit (a4), polyetherketoneetherketoneketone (for example, "VICTREX ST" manufactured by Victrex) and the like can be exemplified. As a resin having a repeating unit (a5), polyetheretherketoneketone and the like can be exemplified. In the repeating unit composed of an arylene group, an ether group and a carbonyl group, the ratio of the ether segment (E) to the ketone segment (K) is, for example, E / K=0.5 to 3, preferably about 0.5 to 2.0. The ether segment imparts flexibility to the molecular chain, and the ketone segment imparts rigidity to the molecular chain. Therefore, the more ether segments there are, the faster the crystallization rate is, and the higher the crystallinity that can be finally achieved is, and the more ketone segments there are, the higher the glass transition temperature and melting point tend to be. These aromatic polyetherketone resins can be used alone or in combination of two or more.

[0077] Among these aromatic polyetherketone resins, an aromatic polyetherketone resin having any one of the repeating units (a1) to (a4) is preferred. For example, as the aromatic polyetherketone resin, at least one resin selected from the group consisting of polyetherketone, polyetheretherketone, polyetherketoneketone and polyetherketoneetherketoneketone is preferred. Furthermore, at least one resin selected from the group consisting of polyetherketone, polyetheretherketone and polyetherketoneketone is more preferred. In particular, polyetherketoneketone is preferred because of improved wire processability and low dielectric constant.

[0078] The melting point of the aromatic polyetherketone resin is preferably 300° C. or higher, and more preferably 320° C. or higher. When the melting point is within the above range, the heat resistance of the obtained molded article can be improved.

[0079] The glass transition temperature (Tg) of the aromatic polyetherketone resin is preferably 130°C or higher. It is more preferably 135°C or higher, and even more preferably 140°C or higher. By having a glass transition temperature in the above range, an insulated wire having excellent heat resistance can be obtained. The upper limit of the glass transition temperature is not particularly limited, but is preferably 220°C or lower, and more preferably 180°C or lower, from the viewpoint of moldability.

[0080] The glass transition temperature is measured in accordance with JIS K7121 using a differential scanning calorimeter (DSC) apparatus under measurement conditions consisting of a temperature increase rate of 20° C. / min.

[0081] In the coating composition, the total amount of the FEP particles and the binder resin is preferably 15% to 35% by mass, more preferably 18% by mass or more, and more preferably 30% by mass or less, relative to the total amount of the fluororesin, the binder resin, and the liquid medium constituting the coating composition. If the total amount of the FEP particles and the binder resin is within the above range, a coating film having better adhesion to a substrate can be formed.

[0082] The coating composition disclosed herein contains a liquid medium that dissolves the binder resin and serves as a dispersion medium for the FEP particles. Such a liquid medium is not particularly limited, and for example, at least one selected from the group consisting of N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, and N,N-dimethylacetamide can be used.

[0083] The amount of the liquid medium to be blended can be selected within a range that allows the coating composition to have coating film-forming properties and a coating viscosity suitable for a coating method.

[0084] The coating composition of the present disclosure may further contain conventionally used additives such as pigments, brighteners, antimicrobial agents, and fillers as other components within a range that does not impair the effects of the coating composition of the present disclosure.

[0085] The total amount of the other components may be 50% by mass or less of the total amount of the FEP particles and the binder resin in order not to reduce the non-adhesiveness of the coating film formed of the coating composition.

[0086] It should be noted that the coating composition of the present disclosure may contain a coloring pigment. Examples of the coloring pigment include titanium oxide, cobalt oxide, carbon, and chromium oxide.

[0087] The content of the coloring pigment is preferably 0.01% by mass or more, more preferably 0.03% by mass or more relative to the total mass of the FEP resin and the binder resin. When the coloring pigment is less than 0.01% by mass, the target coloring may not be obtained. In addition, the content of the coloring pigment is preferably 5% by mass or less, more preferably 3% by mass or less relative to the total mass of the FEP resin and the binder resin. When the coloring pigment exceeds 5% by mass, the brittleness of the obtained coating film becomes significant, sometimes resulting in reduced wear resistance.

[0088] In addition, the coating composition of the present disclosure may contain a filler. By containing a filler, the hardness of the coating film is usually improved. In this case, the wear of the coating film itself is easily suppressed during sliding, and on the other hand, the wear of the object member is sometimes promoted during sliding. Therefore, whether it is necessary to contain a filler and its mixing amount is preferably appropriately selected according to the use environment of the sliding portion.

[0089] When selecting filler materials, the new Mohs hardness can be used as an indicator. The new Mohs hardness is a scale that evaluates the relative hardness of a material in the range of 1 to 15.

[0090] In the case where it is required to suppress the wear of the object member, it is preferred to use a filler with a new Mohs hardness of less than 7. As such a filler, there is no particular limitation, and examples thereof include talc (new Mohs hardness 1), graphite (new Mohs hardness 2), boron nitride (new Mohs hardness 2), mica (new Mohs hardness 3), aluminum hydroxide (new Mohs hardness 3), calcium carbonate (new Mohs hardness 3), calcium fluoride (new Mohs hardness 4), zinc oxide (new Mohs hardness 4-5), tricalcium phosphate (new Mohs hardness 5), iron oxide (new Mohs hardness 6), etc. Among them, from the aspect of taking into account the wear suppression of the coating film itself and the wear suppression of the object member during sliding, it is preferably selected from at least one of the group consisting of graphite and iron oxide. In addition, two or more of these may be used in combination.

[0091] On the other hand, in the case of particularly requiring to suppress the wear of the coating film itself, it is preferred to use a filler with a new Mohs hardness of more than 7. As such a filler, it is not particularly limited, and can include, for example, silicon dioxide (new Mohs hardness 7), glass flakes (new Mohs hardness 7), silicon dioxide (new Mohs hardness 7), quartz (new Mohs hardness 8), topaz (new Mohs hardness 9), garnet (new Mohs hardness 10), zirconium oxide (new Mohs hardness 11), tantalum carbide (new Mohs hardness 11), aluminum oxide (new Mohs hardness 12), tungsten carbide (new Mohs hardness 12), silicon carbide (new Mohs hardness 13), boron carbide (new Mohs hardness 14), diamond (new Mohs hardness 15), fluorinated diamond (new Mohs hardness 15), cubic boron nitride (new Mohs hardness 15), etc. Wherein, from the aspect of reducing the wear of the object member, it is preferably selected from at least one of the group consisting of silicon dioxide, quartz and aluminum oxide. In addition, two or more of these can also be used in combination.

[0092] The coating composition disclosed in the present invention has excellent wear resistance and can be used as a coating material for sliding materials that can be used in high temperature and high heat generation environments. As specific products, air conditioning compressor pistons, inclined plates, scroll compressor components, etc. can be cited. It is particularly preferably used for automobile air conditioning compressor pistons. Under more demanding conditions, it is preferred to use a filler with a new Mohs hardness of 7 or more. According to the expectations of the customer, a low-hardness filler or a high-hardness filler can be used, and a wide range of filler selections can be made. The substrate, coating method, etc. in this use can be carried out based on a known method.

[0093] The average particle size of the primary particles of the filler is preferably 0.1 μm or more, more preferably 0.3 μm or more, and further preferably 0.5 μm or more. The average particle size of the primary particles of the filler is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less.

[0094] The average particle size of the primary particles of the filler can be measured as follows. First, the particles in the field of view are photographed using a transmission electron microscope or a scanning electron microscope. And, for the 300 primary particles constituting the agglomerate on the two-dimensional image, the longest length (maximum length) of the inner diameter of each particle is calculated. The average value of the maximum length of each particle is taken as the average particle size of the primary particles.

[0095] The content of the filler is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 12% by mass or less relative to the total mass of the FEP resin and the binder resin. When the filler exceeds 20% by mass, the brittleness of the resulting coating becomes significant, sometimes resulting in a reduction in wear resistance.

[0096] The coating composition of the present disclosure can be produced by a conventional method, for example, by stirring and mixing the components using a stirring and mixing device such as a ball mill, a three-roll mill, or a disperser.

[0097] From the viewpoint of coating properties, the solid content concentration of the coating composition of the present disclosure is preferably 10% by mass to 50% by mass, more preferably 15% by mass or more, and more preferably 35% by mass or less.

[0098] The present disclosure also relates to a coating film, characterized in that it is formed from the above coating composition.

[0099] The coating film obtained from the coating composition is excellent in coating film strength and also excellent in sliding property. The thickness of the coating film is usually 5 μm to 100 μm, preferably 10 μm to 50 μm.

[0100] The thickness can be measured using an eddy current film thickness meter (manufactured by Kett Electric Laboratory).

[0101] Furthermore, the present disclosure also relates to a laminated body characterized by having a coating film formed from the above-mentioned coating composition on a substrate.

[0102] The coating composition disclosed in the present invention can be applied to a variety of coated objects, so the substrate is not particularly limited. For example, materials composed of metals such as aluminum, stainless steel [SUS], and iron; heat-resistant resins; and ceramics can be cited, and materials composed of metals are preferred. The metal can be a single metal or an alloy.

[0103] From the viewpoint of improving the adhesion with the coating film, the substrate is preferably subjected to a surface roughening treatment such as sandblasting and / or a chemical conversion treatment using phosphate or the like before application of the coating film.

[0104] The average surface roughness [Ra] of the substrate is preferably 2 μm to 10 μm. The average surface roughness is a value measured in accordance with JIS D0601.

[0105] The coating film can be formed by applying the coating composition on a substrate. The coating composition can be applied by any known method, such as spray coating, coating with a roller, etc. The coating can also be applied, and the coating composition can be dried at 80°C to 150°C and then fired as desired. The firing temperature is preferably 200°C to 300°C, more preferably 230°C to 280°C.

[0106] The calcination can be performed usually for 15 to 120 minutes, preferably for 30 to 60 minutes.

[0107] Furthermore, the laminate may be subjected to other steps such as surface treatment of the obtained coating film after the above-mentioned firing, processing into a desired shape according to various uses, etc.

[0108] The laminate in the present invention has excellent sliding properties, so it can be used as industrial parts such as sliding components, papermaking rolls, calender rolls, mold demolding parts, housings, valves, valves, gaskets, reels, oil seals, joints, antenna caps, connectors, gaskets, valve seals, embedded bolts, embedded nuts, etc., among which it can be suitably used as sliding components.

[0109] Examples of the sliding member include compressors of automobile air conditioners, swash plates used therein, bearing materials, bearing plates, and precision mechanism sliding members including various gears.

[0110] Example

[0111] The present invention is described below by way of examples. In the examples, % and parts in the blending ratios refer to mass % and mass parts unless otherwise specified. The present invention is not limited to the examples described below.

[0112] The fluororesin particles, binder resin, coloring pigment, and filler used are shown below.

[0113] Fluororesin (FEP) particles A:

[0114] HFP 15.7 mass%, melt flow rate 15 g / 10 min, melting point 267°C, median particle size 0.15 μm

[0115] Fluorine resin (FEP) particles B:

[0116] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 20 g / 10 min, melting point 259°C, median particle size 0.14 μm

[0117] Fluororesin (FEP) particles C: (dispersed in methyl isobutyl ketone)

[0118] HFP 21.8 mass%, melt flow rate 17 g / 10 min, melting point 227°C, median particle size 0.11 μm

[0119] Fluorine resin (FEP) particles D:

[0120] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 2 g / 10 min, melting point 259°C, median particle size 0.14 μm

[0121] Fluorine resin (FEP) particles E:

[0122] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 29 g / 10 min, melting point 258°C, median particle size 0.14 μm

[0123] Fluorine resin (FEP) particles F:

[0124] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 20 g / 10 min, melting point 259°C, median particle size 0.05 μm

[0125] Fluororesin (FEP) particles G:

[0126] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 20 g / 10 min, melting point 259°C, median particle size 45 μm

[0127] Fluorine resin (FEP) particles H:

[0128] HFP 16.0 mass%, PPVE 2.6 mass%, melt flow rate 20 g / 10 min, melting point 259°C, median particle size 60 μm

[0129] Fluororesin (PFA) particles I:

[0130] PPVE 4.1 mass%, melt flow rate 29 g / 10 min, melting point 315°C, median particle size 0.30 μm

[0131] Fluororesin (PTFE) particles J: (dispersed in methyl isobutyl ketone)

[0132] Melting point 329℃, median particle size 0.25μm

[0133] Fluororesin (PTFE) particles K:

[0134] Melting point 329℃, median particle size 4.1μm

[0135] Binder resin L:

[0136] Polyamide-imide varnish HPC-5000 manufactured by Showa Denko Materials Co., Ltd., solid content: 30% by mass, main solvent: N-methyl-2-pyrrolidone

[0137] Binder resin M:

[0138] Polyamide-imide varnish Elan-tech 603G manufactured by ELANTAS, solid content: 35% by mass, main solvent: 3-methoxy-N, N-dimethylpropionamide

[0139] Binder resin N: polyetherimide varnish prepared by dissolving ULTEM1000F3SP manufactured by SABIC in N-methyl-2-pyrrolidone, solid content: 25 mass %

[0140] Binder resin O:

[0141] Polyimide varnish prepared by dissolving AURUM PD450 manufactured by Mitsui Chemicals, Inc. in N-methyl-2-pyrrolidone, solid content: 25% by mass

[0142] Binder resin P:

[0143] Polyetheretherketone dispersion prepared by dissolving KT-820 manufactured by Solvay Specialty Polymers in N-methyl-2-pyrrolidone, solid content: 25% by mass

[0144] Coloring Pigment Q:

[0145] Titanium oxide manufactured by Furukawa Chemical Co., Ltd. (FR-22, average particle size 0.6 μm)

[0146] Coloring Pigment R:

[0147] Carbon black manufactured by Mitsubishi Chemical Corporation (MA-100, average particle size 0.02 μm)

[0148] Filling material S:

[0149] Fujifilm Wako Pure Chemical Industries, Ltd. talc (Wako grade 1, average particle size 8 μm), new Mohs hardness 1

[0150] Filling material T:

[0151] Graphite manufactured by Nippon Graphite Industries (J-CPB, average particle size 5 μm), new Mohs hardness 2

[0152] Filling material

[0153] Quartz made by Denka (fused silica FB-5D, average particle size 4.7 μm), new Mohs hardness 8

[0154] Filling material V:

[0155] Zirconia manufactured by Daiichi Kizenso Chemical Industry Co., Ltd. (DK-3CH, average particle size 14 μm), new Mohs hardness 11

[0156] Filling material W:

[0157] Silicon carbide manufactured by Shinano Electric Refining Co., Ltd. (GC2500, average particle size 5.5μm), new Mohs hardness 13

[0158] (Examples 1 to 20, Comparative Examples 1 to 9)

[0159] One or more of fluororesin particles A to K as fluororesins, any one of binder resins L to P as binder resins, and N-methyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide and methyl isobutyl ketone are mixed at a predetermined mass ratio to obtain a fluororesin dispersion composition.

[0160] In some Examples and Comparative Examples, Q and R as coloring pigments and any one of S to W as fillers were mixed simultaneously during the preparation of the above-mentioned composition to obtain a fluororesin dispersion composition.

[0161] The fluororesin dispersion composition was spray-coated on a degreased aluminum plate, dried at 100°C for 30 minutes, and then calcined at 280°C for 30 minutes to obtain a coating film having a total film thickness of 15 μm.

[0162] As factors of the stability of the compositions obtained in the above Examples and Comparative Examples and the sliding properties of the coatings obtained from the compositions, the time until the coatings were worn away, the wear amount of the counterpart material, and the friction coefficient of the coatings were evaluated as follows.

[0163] (Stability of composition)

[0164] The stability of the composition after preparation (presence of aggregates, etc.) was visually evaluated.

[0165] 0: No coagulants remain during filtration

[0166] ×: Agglomerates and gel-like substances were confirmed during filtration

[0167] (Time until coating wears off)

[0168] The time (seconds) until the coating film peeled off and the aluminum plate was exposed was measured by a reciprocating wear test using a Friction Player (manufactured by RHESCA) at 25° C. and 150° C. Spherical silica (new Mohs hardness 7) was used as a probe.

[0169] (Amount of wear on the counterpart material)

[0170] In the reciprocating wear test using the Friction Player, the weight loss of the spherical silica probe due to wear with the coating film was measured.

[0171] (Coefficient of friction of coating film)

[0172] The friction coefficient of the coating film was measured using TriboGear (manufactured by Shinto Scientific Co., Ltd.).

[0173] (Surface segregation rate of fluorine atoms)

[0174] The surface of the fluororesin coating film was subjected to EDX (energy dispersive X-ray analysis) to measure the depth of 0.5 μm to 1 μm from the surface, and the ratio (mass %) of fluorine atoms segregated on the surface was calculated.

[0175] [Table 1]

[0176] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Fluorine resin (FEP) particles A 13.30 Fluorine resin (FEP) particles B 13.30 11.43 15.18 17.08 Fluorine resin (FEP) particles C 13.30 Fluorine resin (FEP) particles D Fluorine resin (FEP) particles E Fluorine resin (FEP) particles F Fluorine resin (FEP) particles G 13.30 Fluorine resin (FEP) particles H Fluororesin (PFA) Particles I Fluororesin (PTFE) particles J Fluororesin (PTFE) particles K Binder resin L: PAI varnish (NMP) 19.00 19.00 19.00 19.00 25.39 12.66 6.36 Binder resin M: PAI varnish (MPA) Binder resin N: PEI varnish (NMP) Binder resin O: PI varnish (NMP) Binder resin P: PEEK dispersion (NMP) Coloring Pigment Q: Titanium Oxide Coloring Pigment R: Carbon Black Filler S: Talc Filling material T: Graphite Filling material U: Quartz Filling material V: Zirconia Filler material W: Silicon carbide N-Methylpyrrolidone 44.65 44.65 44.65 44.65 40.10 49.03 53.53 MPA Methyl isobutyl ketone 23.05 23.05 23.05 23.05 23.06 23.13 23.08 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 Mass ratio of fluororesin to binder resin 70 / 30 70 / 30 70 / 30 70 / 30 60 / 40 80 / 20 90 / 10 Stability of the composition ○ ○ ○ ○ ○ ○ ○ Wear resistance (FP) 15μm, 1kg, 25℃ 1,900 1,780 1,980 1,430 1,770 1,500 1,400 Wear resistance (FP) 15μm, 1kg, 150℃ 1050 900 1150 690 890 780 650 Weight reduction of target material mg ( / 500 times) 0 0 0 0 10 0 0 Friction coefficient 0.07 0.07 0.07 0.07 0.07 0.06 0.06 Surface segregation rate of fluorine atoms [mass %] 73 69 75 59 62 79 81

[0177] [Table 2]

[0178] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Fluorine resin (FEP) particles A Fluorine resin (FEP) particles B 13.30 13.30 13.30 13.30 12.90 12.05 12.05 12.05 Fluorine resin (FEP) particles C Fluorine resin (FEP) particles D Fluorine resin (FEP) particles E Fluorine resin (FEP) particles F Fluorine resin (FEP) particles G Fluorine resin (FEP) particles H Fluororesin (PFA) Particles I Fluororesin (PTFE) particles J Fluororesin (PTFE) particles K Binder resin L: PAI varnish (NMP) 18.46 17.25 17.25 17.25 Binder resin M: PAI varnish (MPA) 16.29 Binder resin N: PEI varnish (NMP) 22.79 Binder resin O: PI varnish (NMP) 22.79 Binder resin P: PEEK dispersion (NMP) 22.79 Coloring Pigment Q: Titanium Oxide 0.08 Coloring Pigment R: Carbon Black 0.43 Filler S: Talc 1.80 Filling material T: Graphite 1.80 Filling material U: Quartz 1.80 Filling material V: Zirconia Filler material W: Silicon carbide N-Methylpyrrolidone 40.85 40.85 40.85 45.25 46.05 46.05 46.05 MPA 47.40 Methyl isobutyl ketone 23.00 23.05 23.05 23.05 22.83 22.83 22.83 22.83 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 Mass ratio of fluororesin to binder resin 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 Stability of the composition ○ ○ ○ ○ ○ ○ ○ ○ Wear resistance (FP) 15μm, 1kg, 25℃ 1,800 1,620 1,630 1,670 1,890 2,010 2,100 2,990 Wear resistance (FP) 15μm, 1kg, 150℃ 990 830 820 840 1050 1090 1150 1490 Weight reduction of target material mg ( / 500 times) 0 0 0 0 0 0 0 0.1 Friction coefficient 0.06 0.07 0.07 0.07 0.07 0.07 0.07 0.08 Surface segregation rate of fluorine atoms [mass %] 71 73 68 60 67 61 64 65

[0179] [Table 3]

[0180] Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Fluorine resin (FEP) particles A Fluorine resin (FEP) particles B 12.05 12.05 11.35 12.05 12.05 Fluorine resin (FEP) particles C Fluorine resin (FEP) particles D Fluorine resin (FEP) particles E Fluorine resin (FEP) particles F Fluorine resin (FEP) particles G Fluorine resin (FEP) particles H Fluororesin (PFA) Particles I Fluororesin (PTFE) particles J Fluororesin (PTFE) particles K Binder resin L: PAI varnish (NMP) 17.25 17.25 16.25 17.25 17.25 Binder resin M: PAI varnish (MPA) Binder resin N: PEI varnish (NMP) Binder resin O: PI varnish (NMP) Binder resin P: PEEK dispersion (NMP) Coloring Pigment Q: Titanium Oxide 0.04 0.04 Coloring Pigment R: Carbon Black 0.22 0.22 Filler S: Talc Filling material T: Graphite 1.54 Filling material U: Quartz 2.80 Filling material V: Zirconia 1.80 1.54 Filler material W: Silicon carbide 1.80 N-Methylpyrrolidone 46.05 46.05 46.65 46.05 46.05 MPA Methyl isobutyl ketone 22.83 22.83 22.90 22.83 22.83 total 100.0 100.0 100.0 100.0 100.0 Mass ratio of fluororesin to binder resin 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 Stability of the composition ○ ○ ○ ○ ○ Wear resistance (FP) 15μm, 1kg, 25℃ 3,520 4,590 2,880 1,990 3,010 Wear resistance (FP) 15μm, 1kg, 150℃ 1720 2030 1450 1060 1650 Weight reduction of target material mg ( / 500 times) 0.25 0.3 0.16 0 0.21 Friction coefficient 0.09 0.09 0.09 0.08 0.08 Surface segregation rate of fluorine atoms [mass %] 63 62 58 66 63

[0181] [Table 4]

[0182] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Fluorine resin (FEP) particles A Fluorine resin (FEP) particles B Fluorine resin (FEP) particles C Fluorine resin (FEP) particles D 13.30 Fluorine resin (FEP) particles E Fluorine resin (FEP) particles F 13.30 Fluorine resin (FEP) particles G Fluorine resin (FEP) particles H 13.30 Fluororesin (PFA) Particles I 13.30 Fluororesin (PTFE) particles J 13.30 Fluororesin (PTFE) particles K 13.30 Binder resin L: PAI varnish (NMP) 19.00 19.00 19.00 19.00 19.00 19.00 Binder resin M: PAI varnish (MPA) Binder resin N: PEI varnish (NMP) Binder resin O: PI varnish (NMP) Binder resin P: PEEK dispersion (NMP) Coloring Pigment Q: Titanium Oxide Coloring Pigment R: Carbon Black Filler S: Talc Filling material T: Graphite Filling material U: Quartz Filling material V: Zirconia Filler material W: Silicon carbide N-Methylpyrrolidone 44.65 44.65 44.65 44.65 44.65 44.65 MPA Methyl isobutyl ketone 23.05 23.05 23.05 23.05 23.05 23.05 total 100.0 100.0 100.0 100.0 100.0 100.0 Mass ratio of fluororesin to binder resin 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 70 / 30 Stability of the composition × ○ ○ × ○ ○ Wear resistance (FP) 15μm, 1kg, 25℃ - 970 770 - 1040 950 Wear resistance (FP) 15μm, 1kg, 150℃ - 400 390 - 490 480 Weight reduction of target material mg ( / 500 times) - 0 0 - 0 0 Friction coefficient - 0.09 0.1 - 0.09 0.09 Surface segregation rate of fluorine atoms [mass %] - 40 37 - - -

[0183] [Table 5]

[0184] Comparative Example 7 Comparative Example 8 Comparative Example 9 Fluorine resin (FEP) particles A Fluorine resin (FEP) particles B 9.52 18.03 Fluorine resin (FEP) particles C Fluorine resin (FEP) particles D Fluorine resin (FEP) particles E 13.30 Fluorine resin (FEP) particles F Fluorine resin (FEP) particles G Fluorine resin (FEP) particles H Fluororesin (PFA) Particles I Fluororesin (PTFE) particles J Fluororesin (PTFE) particles K Binder resin L: PAI varnish (NMP) 19.00 31.74 3.16 Binder resin M: PAI varnish (MPA) Binder resin N: PEI varnish (NMP) Binder resin O: PI varnish (NMP) Binder resin P: PEEK dispersion (NMP) Coloring Pigment Q: Titanium Oxide Coloring Pigment R: Carbon Black Filler S: Talc Filling material T: Graphite Filling material U: Quartz Filling material V: Zirconia Filler material W: Silicon carbide N-Methylpyrrolidone 44.65 35.75 55.80 MPA Methyl isobutyl ketone 23.05 23.00 22.98 total 100.0 100.0 100.0 Mass ratio of fluororesin to binder resin 70 / 30 50 / 50 95 / 5 Stability of the composition ○ ○ ○ Wear resistance (FP) 15μm, 1kg, 25℃ 900 1,200 780 Wear resistance (FP) 15μm, 1kg, 150℃ 430 500 430 Weight reduction of target material mg ( / 500 times) 0 0 0 Friction coefficient 0.07 0.1 0.07 Surface segregation rate of fluorine atoms [mass %] - 45 88

[0185] This indicates that the coating composition of the present disclosure can stably contain a high degree of fluororesin particles. In addition, in the obtained coating film, the fluororesin is also localized on the surface, indicating excellent abrasion resistance.

[0186] Industrial Applicability

[0187] Since the coating composition of the present disclosure has the above-mentioned constitution, it is possible to form a coating film having excellent sliding properties. Since the laminate of the present disclosure has excellent sliding properties, it can be suitably used as an industrial part such as a sliding member.

Claims

1. A coating composition comprising tetrafluoroethylene / hexafluoropropylene copolymer particles, a binder resin and a liquid medium, characterized in that: The binder resin is at least one selected from the group consisting of polyamideimide resin, polyetherimide resin, polyimide resin and polyaryletherketone resin, The tetrafluoroethylene / hexafluoropropylene copolymer particles have a melt flow rate of 10 g / 10 minutes to 25 g / 10 minutes, a melting point of 270° C. or less, and a median particle size D50 of 0.1 μm to 50 μm. The mass ratio of the tetrafluoroethylene / hexafluoropropylene copolymer particles to the binder resin is 55 / 45 to 94 / 6.

2. The coating composition according to claim 1, wherein The liquid medium contains at least one selected from the group consisting of N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, and N,N-dimethylacetamide.

3. The coating composition according to claim 1 or 2, further comprising a coloring pigment. 4 . The coating composition according to claim 1 , further comprising a filler.

5. A coating film, characterized in that: The coating composition is formed from the coating composition according to any one of claims 1 to 4.

6. A laminate, characterized in that: A coating film formed from the coating composition according to any one of claims 1 to 4 is provided on a substrate.

7. The laminate according to claim 6, wherein: The substrate is a metal substrate. The laminate according to claim 6 or 7, which is a sliding member.

Citation Information

Patent Citations

  • Non-stick finish for molded parts

    JP2002516618A

  • Coating composition and coated article

    JP2007238686A

  • Reed valve for EGR device and method for producing the same

    JP2012149610A

  • Fluororesin film, method for producing fluid dispersion and method for producing base material having fluororesin film

    JP2020037661A

  • Fluororesin film, method for producing fluid dispersion and method for producing base material having fluororesin film

    JP2020037662A